Preterm Infants’ Follow-Up Program at a Public Hospital in Buenos Aires: Two-Decade Study - Aspres, N.; Schapira, I.; Benitez, A.; Galindo, A.; Brundi, M.; Kasten, L.; Feld, V.; Granovsky, G.; Allignani, G.; Fiorentino, A.; Cuneo-Libarona, M.; Vivas, S.; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Objectives: To analyze temporal trends of mortality, morbidity, growth and neurodevelopment until 2 years of corrected age (CA) of very low birth weight infants (VLBWI) born between 1986- 2005 in Ramon Sardá Maternal Infant Hospital (RSMIH). Methods: Descriptive temporal trend study divided in 5 quinquenniums. 1255 VLBWI were born at RSMIH between 1986-2005; 46 were excluded (genetic syndromes, major congenital malformations, confirmed intrauterine infections), 84 were referred out and 1125 were studied. Birth weight (BW), gestational age (GA); morbidity; growth; neurodevelopment at 1 and 2 years of CA; neurological and sensorial disorders, antenatal steroids use, breastfeeding; rehospitalizations; mothers´ age and years of schooling and Unsatisfied Basic Needs Index (UBNI) were recorded. Results: Survival rates increased during the last two periods, especially in <1000g BW infants despite the decrease in GA and BW. Children receiving surfactant (Sf), parenteral nutrition (PN) and antenatal steroids (AS) in the last quinquennium obtained better results in growth (40 weeks GA and 1 CA). The use of these therapies increased greatly in the last decade. Also breastfeeding at 40 weeks GA and 4 months tended to be better. Bronchopulmonary dysplasia (BPD) increased. Rehospitalizations (majorly attributable to lower tract infections) and UBNI stayed equal all along. Mothers’ years of schooling increased a little in the last two quinquenniums. Conclusion: In the last quinquennium children tended to be smaller in GA and BW due to an increase in the survival rate as a result of higher technology and appropriate interventions such as AS, PN, Sf, etc.